Clinical characteristics and prognosis in patients with multi-vessel coronary spasm – comparison with those in patients with single-vessel coronary spasm. (14th October 2021) - Teragawa, H; Oshita, C; Akazawa, R; Uchimura, Y; Orita, Y
Abstract: Background: We have sometimes experienced patients with vasospastic angina (VSA), who showed multi-vessel spasm (MVS) on coronary angiography (CAG) and spasm provocation test (SPT). However, it has not been clarified what clinical characteristics VSA patients with MVS have or whether such patients have poor prognosis. Therefore, we compared the clinical characteristics and prognosis in VSA patients with MVS with those in VSA patients with single-vessel spasm (SVS). Methods: One hundred and fifty-two patients (mean age: 67 yrs, 74 men and 78 women) with VSA, in which presence of coronary spasm was assessed in both left coronary artery (LCA) and right coronary artery (RCA) on SPT, were subjected. We defined VSA as the presence of more than 90% narrowing of the epicardial coronary artery on angiograms, accompanied by the usual chest symptoms and/or ischemic ST-T changes on electrocardiogram. On SPT, MVS was defined as the presence of spasm on ≥ two major coronary arteries. Base on the presence of MVS, patients were divided into the following 2 groups: MVS group and SVS group. The frequencies of conventional coronary risk factors, the average times of anginal attack (per month), the findings of SPT such as spasm provocation induced by low dose of acetylcholine (LDA) and total occlusion due to coronary spasm (TOC), the number of coronary vasodilators at discharge, and the major cardiovascular events (MACE) including death of any cause and readmission due to heart failure, acute coronary syndrome and unstable angina, were compared in the two groups. Results: There were 98 patients (64%) in the MVS group and 54 patients (36%) in the SVS groups. The frequencies of conventional coronary risk factors and the average times of anginal attacks (4/month in both groups) were not different in the two groups. The frequencies of LDA (33% in MVS and 17% in SVS, p<0.05) and TOC (12% in MVS, 0% in SVS, p<0.01) were higher in the MVS group than in the SVS group. The average numbers of coronary vasodilators was higher in the MVS group (1.1±0.4) than in the SVS group (0.9±0.4, p<0.01). The frequency of MACE did not differ in the two groups as follows (figure). Conclusions: These findings suggest that there was no clinical characteristic, suggesting the presence of MVS in VSA patients. Such patients may have higher VSA activity on SPT and have more aggressive medications, leading to the similar prognosis in VSA patient with SVS. Funding Acknowledgement: Type of funding sources: None.